2017
DOI: 10.5194/acp-17-8371-2017
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Arctic methane sources at six sites performing continuous atmospheric measurements

Abstract: Abstract. Understanding the recent evolution of methane emissions in the Arctic is necessary to interpret the global methane cycle. Emissions are affected by significant uncertainties and are sensitive to climate change, leading to potential feedbacks. A polar version of the CHIMERE chemistrytransport model is used to simulate the evolution of tropospheric methane in the Arctic during 2012, including all known regional anthropogenic and natural sources, in particular freshwater emissions which are often overlo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 84 publications
2
37
0
Order By: Relevance
“…Emissions from geological sources stem from the GLOGOS database (Etiope, 2015) and amount to 4.0 Tg CH 4 yr −1 in our domain. ESAS emissions are prescribed to 2 Tg CH 4 yr −1 in agreement with the estimate made by Thornton et al (2016a) based on a ship measurement campaign and with the estimate made by Berchet et al (2016) based on atmospheric observations at surface stations. The temporal and geographic variability of the ESAS emissions is based on the description by Shakhova et al (2010), following the modelling framework of Berchet et al (2016).…”
Section: Input Emission Datasupporting
confidence: 68%
See 1 more Smart Citation
“…Emissions from geological sources stem from the GLOGOS database (Etiope, 2015) and amount to 4.0 Tg CH 4 yr −1 in our domain. ESAS emissions are prescribed to 2 Tg CH 4 yr −1 in agreement with the estimate made by Thornton et al (2016a) based on a ship measurement campaign and with the estimate made by Berchet et al (2016) based on atmospheric observations at surface stations. The temporal and geographic variability of the ESAS emissions is based on the description by Shakhova et al (2010), following the modelling framework of Berchet et al (2016).…”
Section: Input Emission Datasupporting
confidence: 68%
“…Most major source types for methane are present in the northern high latitudes: natural wetlands, oil and gas industry, and peat and forest burnings. There are also other sources that have received increasing attention over the past decade: freshwater systems (Walter et al, 2007;Bastviken et al, 2011;Tan and Zhuang, 2015;Wik et al, 2016), subsea permafrost and hydrates in the East Siberian Arctic Shelf (ESAS, in the Laptev and East Siberian seas; Shakhova et al, 2010;Berchet et al, 2016;Thornton et al, 2016a), and terrestrial thermokarst (Wik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…9). Warwick 10 et al (2016) and Thonat et al (2017) showed that the northern wetland CH4 emissions should peak in August-September in order to explain correctly the seasonality of atmospheric CH4 mixing ratios and isotopes measured across the Arctic. Hence the wetland CH4 emissions presented here are peaking approximately one month too early to perfectly match with their findings.…”
Section: Upscaled Ch4 Fluxesmentioning
confidence: 99%
“…Bloom et al, 2017aZhang et al, 2016) and 2) uncertainties related to the key CH4 emission drivers and responses to these drivers (e.g. Bloom et al, 2017a;Saunois et al, 2017). Evaluation of the emission estimates is 5 thus urgently needed, and the results will feed on improvements in process models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation